A Review of Some Indices used for Drought Studies - Agwata, Jones (My University, 2014)
Droughts are serious extreme events that have adverse effects on the physical environment and water resource systems in both developed and developing countries. Consequently, there is need for adequate measures for responding to and mitigating various impacts arising from drought occurrence. The design and implementation of drought mitigation and response strategies requires an understanding of the various indices that are used to examine drought both at single site and in an area. In the case of water resources management during critical drought periods for instance, a means of objectively identifying drought events in terms time and duration of occurrence, magnitude and severity is required. This is possible only using various indices to characterize drought. In this paper, some of the key drought indices are reviewed and their strengths and weaknesses identified.
Keywords: Drought; Index; Severity; Mitigation